Usher syndrome and Nebulin‐associated myopathy in a single patient due to variants in MYO7A and NEB. Issue 12 (30th July 2020) - Maia, Nuno; Soares, Ana Rita; Fortuna, Ana Maria; Marques, Isabel; Gonçalves, Ana; Santos, Rosário; Melo Pires, Manuel; de Brouwer, Arjan P. M.; Jorge, Paula
Abstract: In a patient with Usher syndrome and atypical muscle complaints, we have identified two separate variants in MYO7A and NEB genes by exome sequencing. The homozygous variants in these two recessive genes could explain the full phenotype of our patient. Abstract : In a patient with Usher syndrome and atypical muscle complaints, we have identified two separate variants in MYO7A and NEB genes by exome sequencing. The homozygous variants in these two recessive genes could explain the full phenotype of our patient.